Recent advances in the scientific research on ancient glass and glaze - Gan, Fuxi; Li, Qinghui; Henderson, Julian (Series on archaeology and history of science in China, 2016)
"The aim of the book is to report the recent research development of ancient glass and glazing technology and the historical-cultural exchange of the East and West along the Silk and Steppe Roads. The contents of this book are dedicated to promote the exchanges between researchers in both social and scientific fields. The scope of this book includes the new archaeological findings of ancient glass and faience in the world, the relationship of glassmaking with glazing technology, the development and application of modern techniques used for the characterization of ancient glass and glaze, compound colorants/opacifiers among ancient glass, the early exchanges of culture and techniques used between China and elsewhere along the Silk and Steppe Roads, and so on"--